ANACANTHOTERMES TURKESTANICUS TERMITINING QASHQADARYO VILOYATIDA TARQALISHI - Ruziboyeva, M.R; Raxmatullayev, A.Y (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
ANACANTHOTERMES TURKESTANICUS TERMITINING QASHQADARYO VILOYATIDA TARQALISHI